The search - Jenkins, Jerry B.; Fabry, Chris, 1961-; LaHaye, Tim F. (Wheaton, Ill. : Tyndale Kids, 2000)
Judd, Vicki, Lionel, and other members of the young Tribulation Force rush to find their friend Ryan as World War III erupts around them.
"The struggle to survive"--Cover.
6.4
5-8
Keywords: Eschatology -- Fiction; Fantasy; Friendship -- Fiction; World War III -- Fiction; Eschatology -- Fiction; Friendship -- Fiction; World War III -- Fiction; Fantastic fiction